Implementation Of Elevator Control System Using Raspberry PI - Saad, Muhamad Tarmizi (Universiti Sains Malaysia, 2018)
Making sure the elevators in the building provide a pleasant experience requires regular elevator maintenance, service and support by professionals. Implementation of the proper algorithm in the elevator control system are vital to make sure system to run smoothly. The main purpose of this project is to propose an algorithm to control the movement of the elevator using Raspberry Pi. Instead of using programmable logic controller, a Raspberry Pi was chosen to act as the master controller to perform the logic algorithm that control the movement of the elevator. This choice enabled easier end-user human-machine-interface, convenient data log accessibility, and a wide variety of future expansion opportunities. Raspberry Pi GPIO's have been used for emulating push button behaviour. The system works by receiving the signal from the input button and then control the motor rotation to move the cabin to the desired destination.